2018
DOI: 10.12871/00039829201813
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Derived Neurotrophic Factor (BDNF) and Serotonin Transporter (SERT) in Platelets of Patients with Mild Huntington’s Disease: Relationships with Social Cognition Symptoms

Abstract: Peripheral biological correlates of early-stage Huntington's disease (HD) are currently attracting much interest given their possible use as prognostic predictors of later neurodegeneration.Since deficits in social-cognition processing are present among the initial disease symptoms, aim of this work was to appraise, in blood platelets, Brain-Derived Neurotrophic Factor (BDNF) and serotonin (5-HT) transporter (SERT), two proteins involved in human adaptive behavior as potential biochemical correlates of such di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Blood samples were collected in vacutainer tubes containing K 3 EDTA as anticoagulant or a clot activator for serum separation. The K 3 EDTA vacutainer tubes were centrifuged at 150 g for 15 minutes in order to separate the platelet rich plasma (PRP) from the other cellular elements 75 . Then the PRP samples were transferred in Falcon tubes and centrifuged again together with clot activator tubes at 1500 g for 15 minutes in order to obtain platelet poor plasma (PPP) and platelet pellet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were collected in vacutainer tubes containing K 3 EDTA as anticoagulant or a clot activator for serum separation. The K 3 EDTA vacutainer tubes were centrifuged at 150 g for 15 minutes in order to separate the platelet rich plasma (PRP) from the other cellular elements 75 . Then the PRP samples were transferred in Falcon tubes and centrifuged again together with clot activator tubes at 1500 g for 15 minutes in order to obtain platelet poor plasma (PPP) and platelet pellet.…”
Section: Methodsmentioning
confidence: 99%
“…The K 3 EDTA vacutainer tubes were centrifuged at 150 g for 15 minutes in order to separate the platelet rich plasma (PRP) from the other cellular elements. 75 Then the PRP samples were transferred in Falcon tubes and centrifuged again together with clot activator tubes at 1500 g for 15 minutes in order to obtain platelet poor plasma (PPP) and platelet pellet. The clot activator tubes were instead centrifuged only one time, at 1500 g for 15 minutes, in order to obtain serum aliquots.…”
Section: Collection Of Biological Samplesmentioning
confidence: 99%
“…However, in other studies, no differences in serum or plasma BDNF levels were found between HD patients and healthy individuals [97,98]. To make this even more contradictory, one of the recent reports indicates increased levels of BDNF in the platelets of HD patients [99]. In addition, overexpression of BDNF in a HD mouse brain was shown to ameliorate the HD phenotype [100], and the BDNF knockout animals showed consistent symptoms like HD transgenic mice [101].…”
Section: Bdnfmentioning
confidence: 95%
“…However, inconsistent changes have been reported in the peripheral BDNF levels of Huntington’s disease patients. Huntington’s disease patients exhibited moderately increased intra-platelet BDNF levels and significantly reduced cognitive/emotional abilities, suggesting that platelet BDNF did not specifically underlie psychosocial deficits in stage II Huntington’s disease [ 103 ]. By contrast, BDNF levels were decreased in the saliva and plasma of Huntington’s disease patients compared to the control [ 104 , 105 ], although there was no correlation between the BDNF level and motor symptoms and cognitive impairment [ 105 ].…”
Section: Bdnf In Huntington’s Diseasementioning
confidence: 99%